Nurses’ Attitudes Towards People with Dementia: the semantic differential technique - Norbergh, Karl-Gustaf (Nursing ethics, 2006)
One important aspect of the nurse-patient relationship is nurses’ attitudes towards their patients. Nurses’ attitudes towards people with dementia have been studied from a wide range of approaches, but few authors have focused on the structure of these attitudes. This study aimed to identify a structure in licensed practical nurses’ attitudes towards people with dementia.Twenty-one group dwelling units for people with dementia at 11 nursing homes participated in the study. A total of 1 577 assessments of 178 patients were sent out to 181 respondents and 1 237 answers were returned. The semantic differential technique was used. The scale had 57 bipolar pairs of adjectives that estimate an unknown number of dimensions of nurses’ attitudes towards an identified patient. The assessments were analysed using entropy-based measures of association combined with structural plots. The analysis revealed four dimensions, which related to licensed practical nurses’ opinions of the patients: an ethical and aesthetic dimension; an ability to understand; an ability to experience; and an ability for social interaction. The results of the study indicated that, on the positive to negative attitude continuum, the nurses’ attitudes fell at the positive to neutral end. This is an important finding owing to the personhood perspective, from which it is reasonable to assume that, with a more positive attitude to people with dementia, the prerequisites for person-centred care will improve.